2010
DOI: 10.4049/jimmunol.0904021
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Induced Mitogenic Factor (HIMF/FIZZ1/RELMα) Increases Lung Inflammation and Activates Pulmonary Microvascular Endothelial Cells via an IL-4–Dependent Mechanism

Abstract: Hypoxia-induced mitogenic factor (HIMF), also known as found in inflammatory zone 1 and resistin-like molecule α, belongs to a novel class of cysteine-rich secreted proteins. It exhibits mitogenic and chemotactic properties during pulmonary hypertension-associated vascular remodeling, as well as fibrogenic properties during pulmonary fibrosis. HIMF expression in the lung was reported to be regulated by Th2 cytokines (IL-4 and IL-13) via the transcription factor STAT6 pathway in a bleomycin-induced pulmonary fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
80
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 71 publications
7
80
1
Order By: Relevance
“…48,[57][58][59][60] As an explanation for our unexpected data, the role of RELMα in arterial thickening and remodeling could vary depending on the type of challenge (e.g., hypoxia vs. antigen). 48,61 Comparing the data shown in Figures 5 and 6 suggests that airway eosinophils, neutrophils, myeloid cell activation markers S100a8 and S100a9, and IL-6 are not critical promoters of the severe arterial remodeling response and that IFN-γ is not a critical inhibitor. With respect to the role of IL-6 in severe pulmonary arterial thickening, it is of great interest that in experimental schistosomiasis the IL-6 pathway has recently been shown to have a protective function.…”
Section: Resultsmentioning
confidence: 97%
“…48,[57][58][59][60] As an explanation for our unexpected data, the role of RELMα in arterial thickening and remodeling could vary depending on the type of challenge (e.g., hypoxia vs. antigen). 48,61 Comparing the data shown in Figures 5 and 6 suggests that airway eosinophils, neutrophils, myeloid cell activation markers S100a8 and S100a9, and IL-6 are not critical promoters of the severe arterial remodeling response and that IFN-γ is not a critical inhibitor. With respect to the role of IL-6 in severe pulmonary arterial thickening, it is of great interest that in experimental schistosomiasis the IL-6 pathway has recently been shown to have a protective function.…”
Section: Resultsmentioning
confidence: 97%
“…RELMa has been shown to induce proliferation of vascular smooth muscle cells and endothelial cells [1,31]. Our previous work suggested that RELMa also exerts a chemokine effect on bone marrow progenitor cells.…”
mentioning
confidence: 99%
“…RELMα is a members of the family of resistin-like molecules which is thought to play an important role in pulmonary fibrosis, asthma, hypoxia and silicosis [6,11,12,13]. Further studies have shown thatresistin-like molecules may be involved in the formation of foam cells and the development of angiogenesis and thrombosis, indicating that they support the progression of atherosclerosis [5,14].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that it also has angiogenic and vasoconstrictive properties [5] and that it increases pulmonary arterial pressure and vascular resistance more potently than either endothelin-1 or angiotensin II [6]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation